2016
DOI: 10.3390/molecules21091230
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Synthesis of Structurally Diverse Triazole-Bridged Flavonoid Dimers and Trimers

Abstract: Flavonoids are a large family of compounds associated with a broad range of biologically useful properties. In recent years, synthetic compounds that contain two flavonoid units linked together have attracted attention in drug discovery and development projects. Numerous flavonoid dimer systems, incorporating a range of monomers attached via different linkers, have been reported to exhibit interesting bioactivities. From a medicinal chemistry perspective, the 1,2,3-triazole ring system has been identified as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Synthetic Aβ42 and Aβ42 Hilyte™ Fluor 488 (both from Anaspec, Seraing, Belgium) were prepared as previously described ( 94 ). Briefly, lyophilized Aβ42 (1 mg) was dissolved in ice-cold TFA (200 ml), sonicated at 0 °C for 60 s and then lyophilized overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic Aβ42 and Aβ42 Hilyte™ Fluor 488 (both from Anaspec, Seraing, Belgium) were prepared as previously described ( 94 ). Briefly, lyophilized Aβ42 (1 mg) was dissolved in ice-cold TFA (200 ml), sonicated at 0 °C for 60 s and then lyophilized overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The peptide was prepared as previously described. 30 Briefly, lyophilised Aβ42 (1 mg) was dissolved in ice cold trifluroacetic acid (200 mL), sonicated at 0 °C for 60 s, then lyophilised overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of alkyl chains is achieved through an SN2 reaction with alkyl halides. The 1,2,3-triazolebridged flavonoids can be accessed through an alkynyl ether via click chemistry reactions with azide functionalization (Sum et al, 2016). Additionally, Zou et al (2020) demonstrated that the presence of hydroxyl groups in the B-ring is critical for the antiviral activity of flavonoids (Zou et al, 2020).…”
Section: Structure: Activity Relationshipmentioning
confidence: 99%